Legal Evaluation of the Implementation of Licensing for Small and Medium Enterprises From the Perspective of Legal Certainty (Majalengka Regency Case Study) - M. Zidane Alfauzan; Moh. Patra Aditya; Adyatma Saputra; Raden Handiriono; Triana Justitia Mahardeka (Indonesian Journal of Business Analytics, 2025)
The regulations governing business licensing procedures for Indonesia's small business sector encounter obstacles in implementation and adherence to applicable laws. Law Number 6 of 2023 is a legislative foundation anticipated to streamline the licensing process for small and medium enterprises. However, there are still obstacles to understanding and implementing it. The problems we studied in this study include how to regulate the legal arrangements regarding business license procedures for the small and medium business sector, what the legal consequences are for violations of business license procedures, and how the implementation of Law No. 6 of 2023 on the growth of small and medium enterprises. This study examines the regulation of business licensing procedures for small and medium firms, the legal ramifications of violations of these procedures, and their effects on expanding the small and medium company sector. This study employs a normative juridical legal method, using descriptive analysis of pertinent rules and interviews with important stakeholders as supplementary data sources. This study aims to elucidate the efficacy of licensing requirements for small and medium enterprises and its impact on economic development within the sector.